A SURVEY ON THE COMPARISON ON DCT, DWT AND SVD WATERMARKING TECHNIQUES (International Journal of Engineering Sciences & Management Research, 2016)
Watermarking is a technique that is used in copyright–protection for valuable medias and it belongs to the information hiding field. The main aim of developing watermarking techniques is to protect the copyright of digital media and to maintain the extents of the secret key. Watermarking is measured by four quantities: capacity, security, robustness, and imperceptibility Robustness is one of the crucial important issues in watermarking.This paper aims to present the survey of the comparisonof the techniques in watermarking, which shows that singular value decomposition provides high security and successful recovery of watermark image.